Insights into the flexibility of the T3 loop and GTPase activating protein (GAP) domain of dimeric α and β tubulins from a molecular dynamics perspective. (October 2019) - C, Selvaa Kumar; Gadewal, Nikhil; Choudhary, Rajan kumar; Dasgupta, Debjani
Graphical abstract: Highlights: As per the pairwise alignment report, in β subunit, two glycine residues (Gly 96 and Gly 98 ) were observed in the T3 loop which gets substituted into aspartic acid and alanine (Asp 98 and Ala 100 ) in α subunit. Through molecular dynamics it was confirmed that the presence of glycine residues within the T3 loop of β subunit enhances the domain mobility during GTP hydrolysis. Overall, the presence of glycine residues reduces the dimer compactness and enhances the structural flexibility in the inter-dimer compared to the intra-dimer. Anisotropic network model confirms higher positive correlation motion in intra-dimer compared to the inter-dimer between the T3 loop and GAP domain. Abstract: Tubulin protein is the fundamental unit of microtubules, and comprises of α and β subunits arranged in an alternate manner forming protofilaments. These longitudinal protofilaments are made up of intra- (α-β) and inter-dimer (β-α) interactions. Literature review confirms that GTP hydrolysis results in considerable structural rearrangement within GTP binding site of β-α dimer interface after the release of γ phosphate. In addition to this, the intra-dimer interface exhibits structural rigidity which needs further investigation. In this study, we explored the reasons for the flexibility and the rigidity of the β-α dimer and the α-β dimer respectively through molecular simulation and Anisotropic Normal Mode based analysis. As per the sequence alignment report, two glycine residues (Gly 96 and Gly 98 ) were observed in the T3 loop of the β subunit which get substituted by Asp 98 and Ala 100 in the T3 loop of the α subunit. The higher mobility of glycine residues contributes to the flexibility of the T3 loop of inter-dimer when they come in direct contact with the GTPase Activating Protein (GAP) domain of the subunit. This was confirmed through RMSD, RMSF and Radius of Gyration based studies. Conversely, the intra-dimer exhibited a lower mobility in the absence of glycine residues. As per ANM based analysis, positive domain correlations were observed between T3 loop and GAP domain of intra- and inter- dimeric contact regions. However, these correlation motions were higher in the intra-dimer as compared to the inter-dimer interface. Thus on the basis of our findings, we hypothesize that the higher flexibility of T3 loop and the GAP domain of the inter-dimer is required for structural rearrangement and protofilament stability during hydrolysis. Furthermore, the slightly rigid nature of the T3 loop and the GAP domain of the intra-dimer assists in enhancing the monomer-monomer interaction through the higher positive domain correlation.